2016
DOI: 10.1128/aac.02972-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Engineered Peptides of a Phage Lysin as Effective Antimicrobials against Multidrug-Resistant Acinetobacter baumannii

Abstract: Acinetobacter baumannii is a Gram-negative bacterial pathogen responsible for a range of nosocomial infections. The recent rise and spread of multidrug-resistant A. baumannii clones has fueled a search for alternative therapies, including bacteriophage endolysins with potent antibacterial activities. A common feature of these lysins is the presence of a highly positively charged C-terminal domain with a likely role in promoting outer membrane penetration. In the present study, we show that the C-terminal amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 35 publications
2
99
0
Order By: Relevance
“…We have not found such residues in CfP1 lysin, and therefore, its antibacterial mechanism remains unknown. Covalent modification of lysins with LPS-destabilizing peptides has been also a recent approach to increase the lysin activity against Gramnegative pathogens (Briers et al 2014a, b;Thandar et al 2016). These chimeric proteins have additional peptides of polycationic, hydrophobic, or amphipathic nature, known to interfere with the lipopolysaccharide-stabilizing forces, assisting the lysins to spontaneously penetrate the Gramnegative outer membrane barrier and become active antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…We have not found such residues in CfP1 lysin, and therefore, its antibacterial mechanism remains unknown. Covalent modification of lysins with LPS-destabilizing peptides has been also a recent approach to increase the lysin activity against Gramnegative pathogens (Briers et al 2014a, b;Thandar et al 2016). These chimeric proteins have additional peptides of polycationic, hydrophobic, or amphipathic nature, known to interfere with the lipopolysaccharide-stabilizing forces, assisting the lysins to spontaneously penetrate the Gramnegative outer membrane barrier and become active antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage lysins are classified as peptidoglycan hydrolases, being able to cleave a variety of bonds in the bacterial peptidoglycan. Preliminary in vitro and in vivo studies suggest high efficiency of such peptides to kill A. baumannii , supporting further clinical development [41]. …”
Section: Mdr Bacteriamentioning
confidence: 99%
“…Several rodent studies have suggested that strain-specific phages can improve outcomes from intranasally inoculated lung infection, intraperitoneal sepsis, or wound infections (288,(292)(293)(294). Lysin peptides from phages have also been studied as effective treatments for A. baumannii infections in mice (295,296).…”
Section: Bacteriophagesmentioning
confidence: 99%